Tolvaptan Improves Refractory Ascites and Overall Survival in Cirrhosis: A Meta-Analysis - Kalal, Chetan; Joshi, Harshad; Zanwar, Shankar; Premkumar, Madhumita (Current Internal Medicine Research and Practice Surabaya Journal, 2025)
Introduction: Refractory ascites is a frequent complication associated with liver cirrhosis. Tolvaptan, a V2-receptor antagonist, has shown effectiveness in improving refractory ascites. This meta-analysis sought to assess the effectiveness of tolvaptan in patients suffering from cirrhosis and refractory ascites. Methods: Databases including Google Scholar, Cochrane, ClinicalTrials.gov, PubMed, and PubMed Central were systematically queried to search for papers from January 1, 2020, to August 10, 2023. Eligible publications for this study included all research evaluating body weight reduction and overall survival rates in patients with refractory ascites according to their response to tolvaptan. The meta-analysis included five studies, encompassing 530 patients with cirrhosis and refractory ascites who were treated with tolvaptan. Research characteristics were documented for all included studies, and outcomes were recorded for tolvaptan responders compared to non-responders. Results: The statistical analysis revealed a significant weight reduction in tolvaptan responders in comparison to non-responders, with a risk ratio (RR) of 1.92 and a confidence interval (CI) of 1.12 to 3.31. The results of the heterogeneity analysis performed on the two outcomes, weight reduction and overall survival in tolvaptan responders, were I²=84%, τ²=0.1328, p<0.01, and I²=86%, τ²=0.6006, respectively. Conclusion: The clinical application of tolvaptan improves symptoms in cirrhotic patients with refractory ascites, resulting in increased survival rates. Nonetheless, additional randomized controlled trials of a larger scale are necessary to validate the findings of this study, accurately predict the benefits of tolvaptan, and identify the patients who would derive the most benefit from its use.   Highlights: 1. Our meta-analysis covers the most recent studies and confirms that tolvaptan improves survival rates in cirrhotic patients with refractory ascites, hence reducing morbidity and mortality. 2. Notable weight reduction is seen in patients with refractory ascites who respond to tolvaptan.